Mechanism of Dual Targeting of the Phytochrome Signaling Component HEMERA/pTAC12 to Plastids and the Nucleus. Issue 4 (23rd February 2017) - Nevarez, P. Andrew; Qiu, Yongjian; Inoue, Hitoshi; Yoo, Chan Yul; Benfey, Philip N.; Schnell, Danny J.; Chen, Meng
Abstract : HEMERA/pTAC12 accumulation in the nucleus requires localization to the plastids. Abstract: HEMERA (HMR) is a nuclear and plastidial dual-targeted protein. While it functions in the nucleus as a transcriptional coactivator in phytochrome signaling to regulate a distinct set of light-responsive, growth-relevant genes, in plastids it is known as pTAC12, which associates with the plastid-encoded RNA polymerase, and is essential for inducing the plastomic photosynthetic genes and initiating chloroplast biogenesis. However, the mechanism of targeting HMR to the nucleus and plastids is still poorly understood. Here, we show that HMR can be directly imported into chloroplasts through a transit peptide residing in the N-terminal 50 amino acids. Upon cleavage of the transit peptide and additional proteolytic processing, mature HMR, which begins from Lys-58, retains its biochemical properties in phytochrome signaling. Unexpectedly, expression of mature HMR failed to rescue not only the plastidial but also the nuclear defects of the hmr mutant. This is because the predicted nuclear localization signals of HMR are nonfunctional, and therefore mature HMR is unable to accumulate in either plastids or the nucleus. Surprisingly, fusing the transit peptide of the small subunit of Rubisco with mature HMR rescues both its plastidial and nuclear localization and functions. These results, combined with the observation that the nuclear form of HMR has the same reduced molecular mass as plastidial HMR, support a retrograde protein translocation mechanism in which HMR is targeted first to plastids, processed to the mature form, and then relocated to the nucleus.